Silicophytoliths from a Pampean native tree community (Celtis ehrenbergiana community) and their representation in the soil assemblage - De Rito, María Victoria (2018)
Plant phytolith production and their incorporation into soil assemblages has been studied by diverse authors indifferent regions of theworld,mainly in the Northern Hemisphere and Africa. However, these types of studies arescarce in native plant communities from South America, especially in non-grass communities. The comprehensionof the relation between plant phytolith production and their incorporation into soils is crucial for the interpretationof past environments and vegetation based on fossil phytolith records. The aim of this work is todescribe the silicophytolith production of a Pampean native tree community (Celtis ehrenbergiana community)and the silicophytolith assemblages of the soils, in order to understand the relation between silicophytolith productionand their incorporation in these natural forests. Silicophytoliths from 19 species of these communitieswere extracted through a calcination technique; while soil samples were subjected to routine techniques. Soilsilicophytoliths were counted and described, and their abundances were referred in relation to total soil mineralogy.Morphologies were similar between species and were mainly derived from the epidermal, vascular andsclerenchymatic tissues. Celtis spp. produced abundant diagnostic morphologies, such as cystoliths and plateletechinate silicophytoliths, typical of the genus. Soil assemblages were dominated by grass silicophytoliths andin a lesser proportion by dicotyledons silicophytoliths. However, grasses are scarcely found or absent in actualforests. These results showed that there was not a direct relation between plant silicophytolith production andsoil phytolith incorporation in these forests. As it occurs in different environments worldwide, soilsilicophytoliths are affected by taphonomical processes (fragmentation, dissolution, mobilization, etc.) andthey are not always an exact reflection of phytolith production of local plants. These results indicate that ahigh silicophytolith production in plants (in this case Celtis spp.) is not always reflected in soil assemblages.These aspects should be considered in relation to the interpretation of fossil silicophytolith records.